2005
DOI: 10.1038/nature03796
|View full text |Cite
|
Sign up to set email alerts
|

Deep sub-seafloor prokaryotes stimulated at interfaces over geological time

Abstract: The sub-seafloor biosphere is the largest prokaryotic habitat on Earth but also a habitat with the lowest metabolic rates. Modelled activity rates are very low, indicating that most prokaryotes may be inactive or have extraordinarily slow metabolism. Here we present results from two Pacific Ocean sites, margin and open ocean, both of which have deep, subsurface stimulation of prokaryotic processes associated with geochemical and/or sedimentary interfaces. At 90 m depth in the margin site, stimulation was such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
398
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 405 publications
(439 citation statements)
references
References 29 publications
36
398
2
3
Order By: Relevance
“…6) provide evidence for methanogenesis in Batumi surface sediments. Methanogenesis in sulfate-bearing sediments was previously verified in the Pacific Ocean (Parkes et al, 2005), in the Gulf of Mexico (Orcutt et al, 2005(Orcutt et al, , 2008, and in the Northwestern Black Sea (Knab et al, 2008), as well as during in vitro studies on AOM-performing microbial consortia under the presence of methane and sulfate (Seifert et al, 2006;Treude et al, 2007). Therefore, we conclude that AOM in surface sediments of the Batumi seep area is spatially accompanied by microbial formation of 13 C-depleted methane, which in type I ss gas over-compensates a general 13 C-enrichement in methane left from the AOM.…”
Section: Methane Consumption and Production In Shallow Sedimentsmentioning
confidence: 91%
“…6) provide evidence for methanogenesis in Batumi surface sediments. Methanogenesis in sulfate-bearing sediments was previously verified in the Pacific Ocean (Parkes et al, 2005), in the Gulf of Mexico (Orcutt et al, 2005(Orcutt et al, , 2008, and in the Northwestern Black Sea (Knab et al, 2008), as well as during in vitro studies on AOM-performing microbial consortia under the presence of methane and sulfate (Seifert et al, 2006;Treude et al, 2007). Therefore, we conclude that AOM in surface sediments of the Batumi seep area is spatially accompanied by microbial formation of 13 C-depleted methane, which in type I ss gas over-compensates a general 13 C-enrichement in methane left from the AOM.…”
Section: Methane Consumption and Production In Shallow Sedimentsmentioning
confidence: 91%
“…The sequences delineating the MCG were described by Inagaki et al (2003), but the same clade had been observed before and either called the Terrestrial Miscellaneous Crenarchaeotic Group (Takai et al, 2001) or Group 1.3 (Jurgens et al, 2000). Members of the MCG have been hypothesized to be numerically and ecologically important in oceanic deep subsurface sediments because they often dominate archaeal clone libraries using 16S rRNA genes (Parkes et al, 2005) as well as 16S rRNA (Biddle et al, 2006), which is often rapidly degraded in inactive cells and may reflect the active population (Felske et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that microbial abundance and activity increase a few tens of centimetres to metres around these geologic interfaces in both marine (Parkes et al 2005) and terrestrial ) subsurface environments. A study of lignites that were interbedded with sand and silt layers ) revealed that the concentration of intact phospholipids, a marker for living micro-organisms, was lowest in the lignite, but increased in the silt layer immediately below the lignite before decreasing again with increasing distance from the lignite.…”
Section: Introductionmentioning
confidence: 99%